Using of Glycerol and DMSO for Leptospira interrogans Cryopreservation - Ukhovskyi, Vitalii V.; Paliy, Anatoliy P.; Tarasov, Oleksandr A.; Ukhovska, Tetiana Ðœ.; Paliy, Andriy P. (Problems of Cryobiology and Cryomedicine, 2019)
Probl Cryobiol Cryomed 2018; 29(1):102â€“106Â